Releasing latent Toxoplasma gondii cysts from host cells to the extracellular environment induces excystation. Issue 12 (November 2021) - Saito, Taizo; Masatani, Tatsunori; Kitoh, Katsuya; Takashima, Yasuhiro
Graphical abstract: Highlights: The trigger of Toxomplasma gondii cyst excystation is environmental ion composition. Excystation occurs in a solution mimicked extracellular ion composition. A high Na + /K + ratio is required. The presence of Ca 2+ is also required. Abstract: Toxoplasma gondii, an obligate intracellular protozoan parasite, infects a wide variety of mammals and birds. Although T. gondii infects the brain and muscles in its latent cyst form containing bradyzoite stage parasites during chronic infection, when a chronically infected host becomes immunodeficient or is preyed upon by a predator, the latent cyst undergoes excystation. However, it is not yet known how T. gondii recognises the triggers of excystation in the microenvironment surrounding the cyst. In this study, we incubated T. gondii cysts from host cells in several solutions containing a variety of ionic compositions. Excystation occurred in a solution with an ionic composition which mimicked that of the extracellular environment. However, excystation did not occur in a solution that mimicked the intracellular environment. We also found that the specific Na + /K + ratio and the presence of Ca 2+, mimicking the extracellular environment, are required to trigger excystation. To examine whether the stage conversion of bradyzoite to tachyzoite occurs prior to egress, we constructed a gene-modified T. gondii strain expressing a green fluorescent protein specifically in the tachyzoite stage. During the process of cyst reactivation of this strain, green fluorescence was detected prior to excystation. This suggests that stage conversion from bradyzoite to tachyzoite occurs prior to cyst disruption. These results indicate that T. gondii bradyzoites monitor the ionic composition of their surroundings to recognise their expulsion from host cells, to effectively time their excystation and stage conversion.